PyRDFRules : Python wrapper for RDFRules - Douda, Karel (2024)
PyRDFRules is a Python wrapper for interacting with RDFRules, a complex analytical tool for association rule mining in knowledge graphs. RDFRules provides in-built data pre-processing, postprocessing, prediction and optimisations to the AMIE algorithm it utilizes to mine data from the knowledge graphs.